(untitled) (Jurnal Luminous: Riset Ilmiah Pendidikan Fisika, 2021)
This research aimed to analyze the difference of generic science skills of students between guided inquiry learning and problem based learning at SMP Negeri 1 Candi. The methods used in quantitative quasi experimental design. The population in this study was 321 students. The sample was taken by purposive sampling seeing the equality of students generic skills, namely students in the VIII-F and VIII-I class. The data of generic science skills was collected by using test.The technique of data analysis which researchers of used namely one way ANOVA test. The result showed that there was no difference of the generic science skills between the student in the guided inquiry class and the student in the problem based learning class.